Errata - Contemporary changes of thermal conditions in Poland, 1951-2015 - Owczarek, Małgorzata; Filipiak, Janusz (Bulletin of Geography. Physical Geography Series, 2017)
Errata - The main subject of the research whose outcomes are presented in this paper is the spatial and temporal variability of thermal conditions in Poland during the period from 1951 to 2015. The analysis revealed the occurrence of symptoms indicating a systematic and sustained warming. Significant growth is observed in mean and extreme temperatures and their extreme percentiles, as well as in annual number of hot days, warm waves and their duration. In turn, downward trends are noted in series of the annual number of frost days, as well as in the number of cold waves and their duration. The results obtained confirm the thermal pattern determined for the whole region, especially for the southern part of the Baltic Sea Basin.